Assessing the Cytotoxicity and Wound Healing Potential of Pranic Healing Colours: An in vitro Study on HaCaT Cell Line (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Pranic Healing is a complementary therapy that uses specific colours to enhance the healing of wounds. Objectives Our research sought to investigate the impacts of integrating various Pranic Healing (PH) colours on wound healing. Materials and Methods HaCaT cells were subjected to cytotoxicity and scratch assays. After wound formation, Pranic colours were projected to the cells individually or in combination. The data was collected at the 24th, 48th and 72nd hr. Results Cytotoxicity tests revealed PH colours were safe. Cell viability did not differ significantly between groups, according to the Kruskal-Wallis test. However, there were substantial variations in the impact that PH colours had. In contrast, a combination of colours proved more effective than single colours in promoting wound healing. Conclusion The study underscores the potential impact of PH colours on enhancing cell health and promoting wound healing.
Keywords: Biofield; Complementary therapy; Prana; Wound healing; Yoga.